Dissociating Affective and Cognitive Theory of Mind in Recently Detoxified Alcohol‐Dependent Individuals. (18th July 2016) - Maurage, Pierre; D'Hondt, Fabien; de Timary, Philippe; Mary, Charlotte; Franck, Nicolas; Peyroux, Elodie
Abstract : Background: Emotional and interpersonal impairments have been widely described in alcohol dependence, and their role in relapse has been clearly established. However, several components of social cognition have not been well explored in this context. Particularly, Theory of Mind (ToM) abilities, which are critical social skills enabling one to understand others' perspectives, and which have been largely investigated in other psychiatric populations, remain to be measured using ecological tasks in individuals with alcohol dependence. This study evaluated ToM abilities in close to real‐life situations among alcohol‐dependent individuals and differentiated its affective and cognitive subcomponents. Methods: Thirty‐two alcohol‐dependent individuals (in their third week of abstinence) and 32 matched healthy controls performed the Movie for Assessment of Social Cognition (MASC), a multiple‐choice task requiring the identification of the emotions, thoughts, and intentions expressed in 45 short video sequences depicting real‐life social interactions. Results: Alcohol‐dependent individuals showed a global ToM impairment, indexed by a reduced MASC global score. However, exploration of ToM's subcomponents showed that the overall deficit was driven by a massive reduction in affective ToM, with the cognitive subcomponent preserved. Conclusions: Ecological ToM evaluation shows that alcohol dependence is not related to a generalized ToM deficit but rather to dissociation between a preserved cognitive subcomponent and an impaired affective one. These results underscore the importance of ecological measures to precisely investigate each subcomponent of social cognition in alcohol‐dependent individuals. They further show that alcohol dependence is closely associated with emotional‐affective impairments, pointing to the need to develop rehabilitation programs focusing on these components in clinical settings. Abstract : Performance (percentage of correct answers) in alcohol‐dependent and healthy control individuals for global score and affective–cognitive subscales of the Movie for Assessment of Social Cognition (MASC), an experimental task exploring Theory of Mind (ToM) abilities (ns, nonsignificant; * p  < 0.001). This figure illustrates that alcohol dependence is not related to a generalized ToM deficit, but to a dissociation between preserved cognitive ToM and impaired affective one. Such ecological evaluation of social cognition shows that emotional‐affective deficits play a crucial role in alcohol dependence.